Structural Equation Modeling for the Influence of Effectiveness, Lifestyle, and Income Level on the Use of E-Wallet Services by Urban Workers’ - Putri Ayu Agustina; Harmi Sugiarti (Jurnal Ilmiah Sains, 2024)
The convenience and advantages that e-wallets offer in transactions have the potential to change people's perception of conventional transactions. This study aims to investigate whether the use of e-wallet services by workers is influenced by factors such as effectiveness, lifestyle, and income level. The data was collected via questionnaires which were randomly distributed amongst 100 workers in Bekasi City and its surroundings. The ordinal data obtained was converted into interval data using the successive interval (MSI) method, which was later analyzed using the Structural Equation Modeling, Partial Least Square (SEM PLS) technique. The results of the study indicate that variables such as effectiveness and lifestyle have a positive and significant impact on workers' interest in using e-wallets, while the income level variable has an insignificant influence on their interest in using e-wallets.